2022
DOI: 10.26508/lsa.202101283
|View full text |Cite
|
Sign up to set email alerts
|

TET2-mediated epigenetic reprogramming of breast cancer cells impairs lysosome biogenesis

Abstract: Methylation and demethylation of cytosines in DNA are believed to act as keystones of cell-specific gene expression by controlling the chromatin structure and accessibility to transcription factors. Cancer cells have their own transcriptional programs, and we sought to alter such a cancer-specific program by enforcing expression of the catalytic domain (CD) of the methylcytosine dioxygenase TET2 in breast cancer cells. The TET2 CD decreased the tumorigenic potential of cancer cells through both activation and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…S4A-B), suggesting a general tendency toward reprogramming of the cancer methylome. We then examined the binding activities of known regulators of DNA methylation, namely, DNMT1, DNMT3B, and TET2, at the DMPs [ 32 , 40 ]. Of the three genes, TET2-binding activity was selectively enriched at Hypo-DMPs in MCF-7 cells (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S4A-B), suggesting a general tendency toward reprogramming of the cancer methylome. We then examined the binding activities of known regulators of DNA methylation, namely, DNMT1, DNMT3B, and TET2, at the DMPs [ 32 , 40 ]. Of the three genes, TET2-binding activity was selectively enriched at Hypo-DMPs in MCF-7 cells (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the relationships between DMPs and DNA methyltransferases and demethylating enzymes, we obtained ChIP-seq data for DNMT3A and DNMT3B (HepG2) from ENCODE and published ChIP-seq data for TET2 (MCF7) [ 32 ]. We obtained multiple independent datasets of FOXA1 binding from ChIP-Seq experiments, including four cancer cell lines (A549, HepG2, and MCF-7 from ENCODE and T47D [ 33 ]) and tissues (colorectal cancer and breast cancer) [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…S10). A previous report showed that IRF9 can be induced by decitabine and TET2-catalytic domain [ 42 ], so there is a large possibility that IRF9 could also be induced by 5-azacytidine and vitamin C combination treatment. In addition, a positive feedback loop between IFR9 and STING has also been reported by Ma et al [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of TET2 Catalytic Domain (TET2-CD) increases the 5hmC levels, which induces and inhibits the expression of thousands of genes that inhibit cell proliferation and migration in MCF-7 BC cells, as well as tumor growth in vivo. Interestingly, TET2-CD alters the 5hmC in binding sites for the V-Myc Avian Myelocytomatosis Viral Oncogene Homolog (MYC) transcription factor in a set of genes involved in lysosome biogenesis [ 81 ]. On the other hand, TET2 knockout decreases the 5hmC levels and increases the 5mC levels, particularly in enhancers, altering the expression of genes, including ERα target genes, by reducing the ERα transcription factor binding.…”
Section: Molecular Mechanisms Of Tet Enzymes In Bcmentioning
confidence: 99%